Intangible assets and the organization of global supply chains - Stefano Bolatto; Alireza Naghavi; Gianmarco I. P. Ottaviano; Katja Zajc Kejžar (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
This paper introduces the concept of intangible assets in sequential supply chains and the importance of their appropriability in the organizational decision of firms. We focus on the quality of intellectual property rights (IPR) institutions, which on top of the hold-up problem between a supplier and the final producer entails an additional risk of imitation as technology may leak to competing producers in the market. The level of IPR enforcement in the location of a supplier can therefore play a crucial role in determining the decision of a final good producer whether to outsource or integrate a particular stage of production. The analysis is performed with Antràs and Chor (2013) in the background, where the position of the input along the supply chain, i.e. its upstreamness, and the degree of sequential complementarity of stage-specific inputs influence the organizational strategy of firms through the incentive structure of supplier investments. Our findings show that introducing intangible assets in sequential supply chain may have the opposite effect of contractibility on outsourcing decision, where only tangible property rights are considered. We argue therefore that the risk of imitation is a relevant feature that needs to be accounted for in the incomplete contract literature. Our theoretical predictions are validated on Slovenian firm-level data.
Keywords: F12; F14; F21; F23; D23; L22; L23; L24; O34; 330; Sequential production; Intellectual property; Intangible assets; Appropriability; Stage complementarity; Upstreamness; Firm organization; Outsourcing; Integration